Organic manure and fertilizer N management strategies improve soil health at different growth stages of pearl millet under pearl millet-wheat sequence - Sunita Sheoran; Dhram Prakash; Dev Raj; Parmod Kumar Yadav; Rameshwar Singh; Rajeev Kumar Gupta; Saud Alamri; Manzer H. Siddiqui; Shahbaz Khan (BMC Plant Biology)
Abstract Background Incorporating organic manure improves soil properties and crop productivity. A long-term study started in October 1967 examined the effects of farmyard manure and nitrogen fertilization on the soil at key growth stages of pearl millet in a pearl millet-wheat cropping system over its 51st cycle. Results Applying 15 Mg of farmyard manure (FYM) per hectare in both growing seasons significantly boosted soil organic carbon (SOC), dissolved organic carbon (DOC), and key nutrients compared to one-season application. SOC levels reached 9.1–11.0% with FYM15, outperforming FYM10 and FYM5. The effectiveness order was FYM15 > FYM10 > FYM5 > FYM0. Chemical nitrogen fertilization also enhanced soil properties, with FYM15 improving DOC, available nitrogen, and enzyme activities during various growth stages. Conclusions Principal component analysis (PCA) effectively distinguished soil variables and treatments, with β-glucosidase and arylsulfatase activity (ARA) showing the highest loading (0.294) in the first principal component (PC1), followed by dissolved organic carbon (DOC) at 0.292 and dehydrogenase activity (DHA) at 0.291. A strong polynomial relationship was noted between soil organic carbon (SOC) and various soil properties, with R² values between 0.93 and 0.99. The FYM15 x N120 treatment improved soil health in North-West India’s sandy loam soils during both seasons.